Analysis of Feminism in the Novel "Raumanen" by Marianne Katoppo and the Novel "Nayla" by Djenar Maesa Ayu, and Its Implementation in the Learning Process in High Schools - Nurul Khairani; Andi Tenri Sua; Muhammad Idris (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2022)
This study aims to find out: feminism contained in Marianne Katoppo's Raumanen novel and Djenar Maesa Ayu's Nayla novel, as well as its implementation in learning in high school/equivalent. The theory used in this study is the theory of feminism, the theory of feminism is a theory as an attempt by women to show their existence in various fields without having to have restrictions in terms of gender and gender. This research is a library research. The method used to collect data is the document method. This research data was collected and then analyzed using a qualitative descriptive method to describe Raumanen's novel, and Nayla's novel. Content analysis method to reveal the deep feminist movement in Raumanen's and Nayla's novels. The results of this study are feminism in Raumanen's novel, namely, activists in student organizations and single mothers. Whereas in the novel, Nayla is brave, a discotheque lighting worker, and an author with a sex theme. The author's suggestions for future research are expected to be able to study and research the novel Nayla by Djenar Maesa Ayu, and also the novel Raumanen by Marianne Katoppo using different analysis as a form of knowledge of Indonesian language and literature.